2012
DOI: 10.1007/s11630-012-0559-9
|View full text |Cite
|
Sign up to set email alerts
|

Control of secondary flow in a low solidity circular cascade diffuser

Abstract: Kyushu University (retired)According to the previous experimental works on the low solidity circular cascade diffuser (LSD), a pressure recovery of a centrifugal blower was improved by the LSD significantly in a wide range of flow rate, and the pressure recovery was improved further by the LSD with a tandem cascade in comparison with the LSD with a single-row cascade. In the present study, the flow behavior in the LSD with the tandem cascade has been analyzed numerically by using the commercial CFD code of ANS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Senoo et al tested a series of diffusers with backward curved centrifugal impellers, and demonstrated that a diffuser with a small-solidity cascade has a wide range of stable operations comparable to that of a vaneless diffuser, and the diffuser achieves considerably better pressure recovery [12]. Oh et al [13] and Sakaguchi et al did some research work on tandem cascade diffusers and obtained similar conclusions [14]. Saha and Roy [15,16] carried out a series of research on the new design method of low aspect ratio tandem cascade and the control ability of variable angle tandem cascade on non-design point flow.…”
Section: Introductionmentioning
confidence: 89%
“…Senoo et al tested a series of diffusers with backward curved centrifugal impellers, and demonstrated that a diffuser with a small-solidity cascade has a wide range of stable operations comparable to that of a vaneless diffuser, and the diffuser achieves considerably better pressure recovery [12]. Oh et al [13] and Sakaguchi et al did some research work on tandem cascade diffusers and obtained similar conclusions [14]. Saha and Roy [15,16] carried out a series of research on the new design method of low aspect ratio tandem cascade and the control ability of variable angle tandem cascade on non-design point flow.…”
Section: Introductionmentioning
confidence: 89%